European consensus on core principles and future priorities for geriatric rehabilitation: consensus statement - Grund, Stefan; Gordon, Adam L.; van Balen, Romke; Bachmann, Stefan; Cherubini, Antonio; Landi, Francesco; Stuck, Andreas E.; Becker, Clemens; Achterberg, Wilco P.; Bauer, Jürgen M.; Schols, Jos M. G. A. (European geriatric medicine, 2020)
The consensus statement about core principles and future priorities of geriatric rehabilitation has the aim to help healthcare providers which need strategies to support older people who have experienced functional decline.
Published online: 13 December 2019
Gesehen am 21.04.2020